2021
DOI: 10.3390/nu13124478
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response of Paraxanthine on Cognitive Function: A Double Blind, Placebo Controlled, Crossover Trial

Abstract: Paraxanthine (PXN) is a metabolite of caffeine that has recently been reported to enhance cognition at a dose of 200 mg. Objective: To determine the acute and short-term (7-day) effects of varying doses of PXN on cognitive function and side effects. Methods: In a double blind, placebo-controlled, crossover, and counterbalanced manner, 12 healthy male and female volunteers (22.7 ± 4 years, 165 ± 7 cm, 66.5 ± 11 kg, 24.4 ± 3 kg/m2) ingested 200 mg of a placebo (PLA), 50 mg of PXN (ENFINITY™, Ingenious Ingredient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
(81 reference statements)
2
10
0
Order By: Relevance
“…Yoo and investigators [34] reported on the first human data involving paraxanthine supplementation, wherein they concluded that acute oral ingestion of a 200 mg dose of paraxanthine may affect short-term memory, reasoning, and response time to cognitive challenges. The outcomes were later confirmed in a dose-response study, confirming that paraxanthine may serve as an effective nootropic nutrient at acute doses as low as 50 mg [35]. Certainly, it remains plausible that the observed increases in nitric oxide could explain some of the observed changes in treadmill endurance performance, as exhibited by the mice in this study.…”
Section: Discussionsupporting
confidence: 74%
“…Yoo and investigators [34] reported on the first human data involving paraxanthine supplementation, wherein they concluded that acute oral ingestion of a 200 mg dose of paraxanthine may affect short-term memory, reasoning, and response time to cognitive challenges. The outcomes were later confirmed in a dose-response study, confirming that paraxanthine may serve as an effective nootropic nutrient at acute doses as low as 50 mg [35]. Certainly, it remains plausible that the observed increases in nitric oxide could explain some of the observed changes in treadmill endurance performance, as exhibited by the mice in this study.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, Kackley and associates [56] reported that ingesting ketogenic salts may attenuate negative aspects of mood associated with diet intervention. Our group has also reported that acute and one-week ingestion of paraxanthine (the compound that caffeine is primarily converted into after ingestion) [33,57], as well as ashwagandha [58], appears to improve short-term memory, reaction times, and/or errors in healthy individuals. These findings are consistent with studies reporting that various nutrients (with and without caffeine) may influence cognitive function.…”
Section: Discussionmentioning
confidence: 90%
“…These findings are consistent with studies reporting that various nutrients (with and without caffeine) may influence cognitive function. Additionally, combining various nootropic nutrients may provide some additive and/or synergistic benefit [7,9,10,14,27,33,47,54,55,57,59,60].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is predominantly found as the major metabolite of caffeine, accounting for approximately 70%–72% of ingested caffeine ( Stavric, 1988 ). Paraxanthine has been shown to have several of the same nootropic benefits as caffeine, including improved cognition, short-term memory, sustained attention in heathy adults ( Xing et al, 2021 ; Yoo et al, 2021 ) and beneficial cognitive effects in animal models of Parkinson’s disease ( Xu et al, 2010 ; Xing et al, 2021 ; Yoo et al, 2021 ). Moreover, the beneficial impacts on physical endurance and sports performance that have been observed with caffeine use ( Guest et al, 2021 ) have also been suggested for paraxanthine ( Jäger et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Paraxanthine is also unique from other methylxanthine stimulants in that it seems to possess anxiolytic activity ( Costentin et al, 2009 ; Okuro et al, 2010 ). Although human toxicity studies on paraxanthine are scarce, the few studies that have been conducted in humans demonstrate a lack of adverse events ( Xing et al, 2021 ; Yoo et al, 2021 ). In fact, an improved safety profile for paraxanthine in comparison to caffeine has been suggested based on evidence from preclinical in vitro and in vivo studies ( Weinstein et al, 1975 ; Renner, 1982 ; Nakatsuka et al, 1983 ; York et al, 1986 ; Stavric, 1988 ; Institute of Medicine (U.S.), 2001 ; Gressner et al, 2009 ; Monteiro et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%